2018
DOI: 10.1111/jcmm.13618
|View full text |Cite
|
Sign up to set email alerts
|

Injection of synthetic mesenchymal stem cell mitigates osteoporosis in rats after ovariectomy

Abstract: Osteoporosis is a severe skeletal disorder. Patients have a low bone mineral density and bone structural deterioration. Mounting lines of evidence suggest that inappropriate apoptosis of osteoblasts/osteocytes leads to maladaptive bone remodelling in osteoporosis. It has been suggested that transplantation of stem cells, including mesenchymal stem cells, may alter the trajectory of bone remoulding and mitigate osteoporosis in animal models. However, stem cells needed to be carefully stored and characterized be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Li et al 156 and Chen et al 157 explored the effects of EVs on the osteogenic, proliferation, and migration capabilities of BMMSCs in vitro, and demonstrated that EVs derived from ASCs promoted bone regeneration. Shen et al 158 found that EVs fabricated from BMMSCs contained growth factors secreted by MSCs, and co‐culture with EVs in vitro increased the viability of osteoblast cells. Further in vivo experiments confirmed that injection of EVs mitigated OVX‐induced osteoporosis by reducing cell apoptosis and systemic inflammation, but increasing osteoblast numbers.…”
Section: Perspectivesmentioning
confidence: 99%
“…Li et al 156 and Chen et al 157 explored the effects of EVs on the osteogenic, proliferation, and migration capabilities of BMMSCs in vitro, and demonstrated that EVs derived from ASCs promoted bone regeneration. Shen et al 158 found that EVs fabricated from BMMSCs contained growth factors secreted by MSCs, and co‐culture with EVs in vitro increased the viability of osteoblast cells. Further in vivo experiments confirmed that injection of EVs mitigated OVX‐induced osteoporosis by reducing cell apoptosis and systemic inflammation, but increasing osteoblast numbers.…”
Section: Perspectivesmentioning
confidence: 99%
“…Stem cells release cytokines, chemokines, growth factors, and different types of extracellular vesicles (EVs) as part of their paracrine signaling system. To mimic the biofunction of stem cells, we and other groups have developed synthetic stem cells by loading conditioned medium to coat the cell membrane for injured heart or liver regeneration [ 21 25 ]. We have confirmed the synthetic stem cells’ superior stability even after repeated freeze–thaw cycles while maintaining high therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent further loss of RPE cells, MSCs can be used as a cell source for treatment (Cislo-Pakuluk and Marycz, 2017). Recently, the production of synthetic MSCs through the packaging of MSC-secreted factors into carriers have shown high promise in animal models of osteoporosis (Shen et al, 2018) and acute myocardial infarction (Lee et al, 2017). This method replaces the direct use of MSC in treatment with the secretome, and thus, circumventing certain drawbacks such as reduced transplant survivability (English and Wood, 2013), undesired differentiation (Volarevic et al, 2018), and tumor promotion (Volarevic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%